Cost-Benefit Analysis of Robotic Versus Nonrobotic Minimally Invasive Mitral Valve Surgery. Issue 2 (March 2015) - Hassan, Mohammed; Miao, Yongjie; Lincoln, Joy; Ricci, Marco
<x xml:space="preserve">Abstract</x> Objective To date, a direct comparison of minimally invasive mitral valve repair or replacement (mini-MVR) versus robotic MVR is lacking; therefore, the purpose of this study was to address this deficit and compare mini-MVR with robotic MVR from a cost-benefit perspective. Methods From a total of 759 literature citations, 21 studies were included for statistical comparisons of benefit outcomes, whereas 3 studies and our institutional experience were used to compare costs. Results The total cost per case exceeding that of conventional MVR is approximately $2063.90 for robotic MVR and $271 for mini-MVR. Mean 30-day mortality rates for mini-MVR and robotic MVR groups were 1.24% and 0.55%, respectively [106/8548 vs 6/1089; odds ratio (OR), 2.27; P = 0.052]. The conversion rate to conventional MVR was 0.77% in mini-MVR and 1.83% in robotic MVR (35/5092 vs 22/1046; OR, 0.32; P < 0.001). The rate of neurologic events was 1.32% in mini-MVR and 2.37% in robotic MVR (109/8257 vs 20/845; OR, 0.55; P = 0.02). Postoperative atrial fibrillation was seen in 11.42% of mini-MVR patients and in 19.67% of robotic MVR patients (371/3249 vs 203/1032; OR, 0.53, P < 0.001). Mean cardiopulmonary bypass time was longer in mini-MVR (137.4 vs 130.4 minutes), whereas cross-clamp time was shorter (82.2 vs 96.7 minutes). Conclusions Our comparative analysis provides insights into the clinical benefits versus variable costs relationship related to mini-MVR and robotic MVR.